Hearing impairment and hypoxia ischaemic encephalopathy: Incidence and associated factors. (January 2019) - Fitzgerald, Michael P.; Reynolds, Adam; Garvey, Cliona Mc; Norman, Gary; King, Mary D.; Hayes, Breda C.
Abstract: Objective: To establish the local incidence of hearing loss in newborns with Hypoxic Ischaemic Encephalopathy (HIE) and to identify associated risk factors. Study design: Retrospective Cohort Study. Neonatal Intensive Care Unit (NICU) dual stage hearing screening protocol, including automated otoacoustic emissions (AOAE) and automated auditory brainstem response (AABR) testing. Results: 57 newborns received therapeutic hypothermia for HIE. Twelve babies (21%) died. Audiology data was incomplete in 3 babies. Complete data was available for 42 babies (male n = 24), 4 (9.5%) of whom had hearing impairment. The development of hearing loss was associated with abnormal blood glucose levels (p = 0.006), low Apgar score at 1 min (p = 0.0219) and evidence of multi organ dysfunction [high creatinine (p = 0.0172 and 0.0198) and raised liver transaminases (aspartate aminotransferase (AST) p = 0.0012, alanine aminotransferase (ALT) p = 0.0037)]. An association with gentamicin was not found. Conclusion: This study confirms that hearing impairment is common in term infants who have undergone therapeutic hypothermia for moderate/severe HIE. Blood glucose should be monitored carefully in these infants and developmental surveillance should include formal audiology. Further larger studies are needed to clarify the role, if any, of hypothermia per se in causation of hearing loss and to fully identify risk factors for hearing impairment in this population. What is new: The current study confirms that hearing impairment is common in term infants who have undergone therapeutic hypothermia for moderate/severe HIE. No association between gentamicin use and the development of hearing impairment was found however initial blood glucose outside the normal range was of significance. Other factors associated with hearing impairment were low Apgar scores, greater need for resuscitation and evidence of multi organ dysfunction (renal and liver failure). Highlights: 9.5% of survivors treated with therapeutic hypothermia developed hearing impairment. Hearing impairment was not associated with gentamicin use. Abnormal glucose recordings, Apgar scores and resuscitation were significant factors. Birth weight <50th percentile was also associated with hearing impairment.